Dispersion of Titanium Oxide Nanoparticles in Aqueous Solution with Anionic Stabilizer via Ultrasonic Wave. (24th November 2016) - Tsai, Wen-Bin; Kao, Jui-Yang; Wu, Tzong-Ming; Cheng, Wen-Tung
Abstract : This paper aims to reveal the effects of odium hexametaphosphate (SHMP) and polyacrylic acid (PAA) on dispersion of TiO2 (P25) nanopowder in de-ionic water through ultrasonic horn. We characterized TiO2 suspension by transmission electron microscopy (TEM), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FTIR), zeta potential, and surface contact angle instruments. As shown in the results, particularly, it were noticed that (1) the SHMP has better dispersion than PAA due to electronegativity effect, resulting in that the average particle size of the dispersed titanium dioxide in de-ionic water was roughly 92 nm, and (2) the zeta potential of TiO2 suspension with SHMP can be achieved by 54 mV at pH value of 7.7, causing stronger electrostatic repulsion in the suspension solution, compared with PAA.